2012
DOI: 10.1186/1471-2202-13-38
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole neuroprotection in a parkinson's disease model involves suppression of reactive astrocytosis but not GLT-1 regulation

Abstract: BackgroundRiluzole is a neuroprotective drug used in the treatment of motor neurone disease. Recent evidence suggests that riluzole can up-regulate the expression and activity of the astrocyte glutamate transporter, GLT-1. Given that regulation of glutamate transport is predicted to be neuroprotective in Parkinson's disease, we tested the effect of riluzole in parkinsonian rats which had received a unilateral 6-hydroxydopamine injection into the median forebrain bundle.ResultsRats were treated with intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 49 publications
5
40
0
Order By: Relevance
“…Special controls were performed using omission of the primary antibodies to assess background staining associated to non-selective binding of the secondary antibody. Lastly, the pattern of immunoreactive staining through the hippocampus obtained using CD11b/c, GFAP and GLT-1 primary antibodies was comparable to previous descriptions (Carbone et al, 2012;Langdon et al, 2008;Simao et al, 2012). Following 5 Â 3 min rinses, slides were incubated with 1 mg/ml Hoescht 33342 stain (Invitrogen, Burlington,ON, Canada) for 10 min at room temperature to label cell nuclei.…”
Section: Immunohistochemistrysupporting
confidence: 59%
“…Special controls were performed using omission of the primary antibodies to assess background staining associated to non-selective binding of the secondary antibody. Lastly, the pattern of immunoreactive staining through the hippocampus obtained using CD11b/c, GFAP and GLT-1 primary antibodies was comparable to previous descriptions (Carbone et al, 2012;Langdon et al, 2008;Simao et al, 2012). Following 5 Â 3 min rinses, slides were incubated with 1 mg/ml Hoescht 33342 stain (Invitrogen, Burlington,ON, Canada) for 10 min at room temperature to label cell nuclei.…”
Section: Immunohistochemistrysupporting
confidence: 59%
“…4,31,40 Even though studies have demonstrated that riluzole can upregulate GLT-1 on cultured astrocytes, 3,22 even in the absence of neurons, 8 riluzole does not alter the expression of striatal GLT-1 in a rodent model of Parkinson's disease when given at a dosage (4 mg/kg) comparable to that used here. 9 Therefore, it can be hypothesized that upregulation of spinal GLT-1 with riluzole treatment after a painful nerve root com- pression is likely a secondary mechanism of its neuroprotective properties (Figs. 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, astrocytes and microglia produce a large variety of different mediators that may affect neurons, e.g., direct excitotoxicants, like glutamate, or indirect excitotoxic mediators, such as NO (Bal-Price and Brown 2001;Bal-Price et al 2002;Gandelman et al 2010;Gegg and Clark 1036;Mander et al 2005), lipid mediators/small molecules (Mayo et al 2014;Simon et al 2002;Wang et al 2012), reactive oxygen species (Ma et al 2013), proteases (cathepsin B), cytokines (Lee et al 2013a;Mattson et al 1997), complement factors (Pekny et al 2007;Walker et al 1998), but their respective contribution to human pathology needs further clarification (Lioy et al 2011;Williams et al 2014). Lack of knowledge of the relevant damage mediators has prevented the development of targeted therapies for modulation of astrogliosis, but some drugs like riluzole (Carbone et al 2012) or CEP1347 (Falsig et al 2004b) have astrocyte-modulating properties besides their main mode of action.…”
Section: Introductionmentioning
confidence: 99%